THE SOURCES AND SYMPTOMS OF NERVOUSNESS PRIOR TO AND DURING A SINGER’S PERFORMANCE - Andžāne, Zane; Marnauza, Māra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
Students of vocal performance, as well as professional singers, feel nervousness in front of an audience at concerts, competitions, and exams. The state of nervousness can be a negative factor for the performance of the singer, and therefore it is important for the professional singer to develop not only vocal techniques, but also performance attitudes that help to reduce stage fright. The aim of the study is to analyze the scientific literature about stage fright, its sources, symptoms, and methods of overcoming it. Methods used: analysis of literature, questionnaire. Student self-analysis answers to questionnaire items give evidence, that students feel nervous when performing, and that this negatively influences their command of vocal technique, as well as the artistic interpretation of the song and the artistic quality overall.